ANALISIS KANDUNGAN NITRIT PADA AYAM CRISPY YANG DIJUAL DI KECAMATAN LELES KABUPATEN GARUT TAHUN 2019 - Dadang Muhammad Hasyim (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Sodium nitrite usually used as a preservative agent in meat processed such as chicken crispy. Sodium nitrite used in meat processed because it can inhibit the growth of the bacteria Clostridium botalinum, retains the red color of the meat, and as a flavor enhancer. Excessive use of sodium nitrite can have harmful effects on health. This study aims to determine the sodium nitrite content of chicken crispy sold in Leles District, Garut Regency. The analytical method used is qualitative analysis using BaCl2 and AgNO3 reagents, while quantitative analysis using UV-Vis spectrophotometry at a wavelength of 520 nm. Samples came from 5 street vendors, so samples A, B, C, and E. The results showed that the five positive samples contained sodium nitrite with levels in sample A = 13.075 mg/kg, B = 6.52 mg/kg , C = 13,345 mg/kg, D = 15,705 mg/kg, and E = 21,61 mg/kg. The use of sodium nitrite in crispy chicken sold by street vendors in Leles District, Garut Regency, does not exceed the level permitted by the Food and Drug Agency, which is 30 mg/kg.